Extending group‐III nitrides to the infrared: Recent advances in InN. Issue 5 (30th January 2015) - Mi, Zetian; Zhao, Songrui
<x xml:space="preserve">Abstract</x> Indium nitride (InN) holds the key to extend the operation wavelengths of group‐III nitride optoelectronic devices from the ultraviolet and visible to the near‐infrared. In this Feature Article, Mi and Zhao provide an overview on the recent advances made in InN, including the absence of surface electron accumulation on the grown surfaces and the direct measurement of p‐type conduction.